A comparison of the effectiveness of gargling green tea and black tea on halitosis reduction: Perbandingan efektivitas berkumur air rebusan teh hijau dan teh hitam terhadap penurunan halitosis - Ni Nyoman Gemini Sari; I Gusti Ngurah Putra Dermawan; Ayu Ratih Kusuma Dewi (Makassar Dental Journal, 2023)
Halitosis is a general term used to describe the smell or odor that is not preferred when air is blown, regardless of whether the substance of odor derived from oral or non-oral. Tea (Camellia sinensis) is the most widely consumed beverage in the world communities; green tea and black tea are commonly known. The purpose of this study was to compare the effectiveness of rin-sing the decoction water of green tea and black tea to decrease halitosis. The method used is quasi-experimental study in which subjects was 50 people, divided into two groups: 25 person rinse with decoction water of green tea and 25 person rinse with de-coction water of black tea. Measuring the level of the halitosis in all samples taken before and after treatment. The results show-ed that there were significant differences between the two treatment groups, ie sig. 0.048 amounted less than 5% (p<0.05). The conclusion is rinsing using decoction water of green tea is more effective to eliminate halitosis than rinsing using decoction wa-ter of black tea.